The relationship between school, class and co-curriculum absenteeism on the academic performance of selected secondary school - Yahaya, Azizi; Ramli, Jamaluddin; Hashim, Shahrin; Ibrahim, Mohd. Ali; Zakaria, Zurihanmi (Science Publications, 2009)
Problem statement: The purpose of this study is to identify the relationship between causes of truant, types of truant and activities done during truant against academic achievement among the lower secondary students. Approach: The research instrument used in this study was questionnaire with Likert scale. The respondents for this study were 80 students were randomly chosen as respondents through simple random sampling. The data collected was analyzed by using the Statistical Package for Social Science for Windows (SPSS 11.5). Inferential and descriptive statistics is used to find the mean, frequency and standard deviation. Results: The findings showed that activities done during truant such as helping the family, joining the negative groups, crime is at the low level and working part-time together with loafing are at the medium level. Findings also showed there is no significance relationship between friends, parents, do not like the teacher, do not like the subject and homework with academic achievement and there is significance relationship between family problems with academic achievement. Conclusion: Parents must also pay due attention and control over their children social life to avoid them from picking up the habit of playing truant from school.